Intellectual property in entomology: Analysis and perspective on recent trends in global patent publications - Hamm, Ronda L; Gregg, Anne; Sparks, Thomas C (Pest management science, 2020)
Intellectual property (IP) is an important consideration for entomological research and provides a means to capture value from new discoveries. Herein, we describe an analysis of more than 26 000 patent publications from 2007–2017 related to the field of entomology. These patents were divided among 8000 patent assignees; however, only 5% of the assignees had ≥10 patents. Corporations accounted for the largest share of patents (59%), with individuals (20%), academic institutions (17%) and government organizations (4%) making up the remaining segments. From 2007–2017 the number of entomological patents increased by 400%, with the largest number being from China. However, unlike patents from Europe, Japan or the US, which target a range of countries, the Chinese patents almost exclusively focus on China. Among the array of subjects covered are transgenic insects and plants, repellents, recombinant insect cells, with the highest proportion of patents focused on insecticides (39%), followed by insecticide mixtures (27%) and formulations (21%). The top 30 patent assignees included companies/institutions from China (18), Europe (3), Japan (6) and the US (3). Among the top 12 entities, IP from the US assignees was distributed across insecticides, mixtures and insecticidal traits while those from China were more focused on mixtures. However, given expanding IP numbers from China it is expected that in the future there will be a greater impact on new insecticides and related technologies. © 2020 Society of Chemical Industry The total number of entomology patents filed in China has continued to rise, whereas patents from the US, Japan and the EU have declined in recent years. Japan and the EU have the highest proportion of patents (2007–2017) originating from crop protection companies (CP) relative to the total number of patents from their corresponding geographies.